Integrated rural tourism strategies for cultural landscape conservation in traditional villages of Yunnan, China - Yang, Yiran (2024)
The cultural landscape of traditional Chinese villages holds significant value in preserving national identity and promoting Chinese culture. Rural revitalisation is currently a robust development strategy being implemented in China, with a specific focus on cultural landscape issues. The primary goals of the strategy are enhancing national cultural confidence, safeguarding and utilising cultural heritage, and achieving sustainable development. However, the number of traditional villages is rapidly declining, and the conflict between protection and development is becoming increasingly apparent. Moreover, existing policies and theories are not being effectively implemented. Therefore, it is essential to conduct in-depth research on the sustainable development of cultural landscapes from multiple perspectives. To this end, this study aimed to explore the sustainable development strategy of cultural landscapes in traditional tourism villages in Shaxi Town, Yunnan Province, in response to the issues faced by the site. Specifically, this study’s objectives were to: (i) identify the challenges related to the sustainable development of cultural landscapes in traditional tourism villages in Shaxi Town; (ii) discover the factors influencing the sustainable development of cultural landscapes in traditional tourism villages in Shaxi Town; and (iii) develop a comprehensive framework for the sustainable development of cultural landscapes in traditional tourism villages in Shaxi Town. This study selected six traditional tourism villages in Shaxi Town, Yunnan, as research cases. These villages possess rich cultural landscapes, with Sideng Village being particularly noteworthy. As the only surviving market on the Tea Horse Ancient Road, Sideng Village holds immense cultural heritage value. Based on the perspectives of constructivism and the theory of rural integration, the qualitative method was employed in this study to collect data through in-depth interviews, observations, and text analysis. The research data were analysed using thematic analysis and triangulation. This study’s findings reveal the complex challenges, influencing factors, and strategies related to effectively preserving and developing cultural landscapes in traditional villages. The results provide valuable insights for policymakers, landscape planners, and developers in order for them to protect the cultural landscape of traditional villages while formulating tourism development strategies. By implementing the study’s recommendations, tourism-based traditional villages in Yunnan Province can promote sustainable tourism development, contribute to rural revitalisation, safeguard their heritage, and utilise their cultural landscapes.